Applications of Microbiome Analyses in Alternative Poultry Broiler Production Systems - Shi, Zhaohao; Rothrock Jr., Michael J.; Ricke, Steven C. (Frontiers in Veterinary Science, 2019)
While most of the focus on poultry microbiome research has been directed toward conventional poultry production, there is increasing interest in characterizing microbial populations originating from alternative or nonconventional poultry production. This is in part due to the growing general popularity in locally produced foods and more specifically the attractiveness of free-range or pasture raised poultry. Most of the focus of microbiome characterization in pasture flock birds has been on live bird production, primarily on the gastrointestinal tract. Interest in environmental impacts on production responses and management strategies have been key factors for comparative microbiome studies. This has important ramifications since these birds are not only raised under different conditions, but the grower cycle can be longer and in some cases slower growing breeds used. The impact of different feed additives is also of interest with some microbiome-based studies having examined the effect of feeding these additives to birds grown under pasture flock conditions. Postharvest microbiome research has not been pursued thus far but certainly has merit as more sanitizers are explored for implementation in these processing units. In the future, microbiome research approaches offer unique opportunities to develop better live bird management strategies and design optimal sanitizer approaches for pasture flock poultry production systems.